2005
DOI: 10.1152/ajpregu.00697.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelin in mediating postmenopausal hypertension in a rat model

Abstract: Cardiovascular disease is the leading cause of death in women after menopause. Hypertension, a major cardiovascular risk factor, becomes more prevalent after menopause. The mechanisms responsible for the increase in blood pressure (BP) in postmenopausal women are unknown. We have recently characterized the aged, postestrous-cycling (PMR) spontaneously hypertensive rats (SHR) as a model of postmenopausal hypertension. The purpose of the present study was to determine whether endothelin plays a role in the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 25 publications
3
35
0
4
Order By: Relevance
“…With regard to oxidative stress, aging female SHR respond with reductions in blood pressure to chronic (8 mo) treatment with vitamins E and C (6), which suggests that oxidative stress plays a role in maintaining hypertension with aging in female SHR, although the present data do not indicate that ANG II is involved in mediating the oxidative stress in aging females. We found previously that the increase in blood pressure with aging in female SHR is associated with greater expression of intrarenal endothelin (ET) than in young females (23). In addition, a specific ET type A receptor antagonist decreased blood pressure in aging female SHR, but not to normotensive levels (23), similar to the effect of losartan in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…With regard to oxidative stress, aging female SHR respond with reductions in blood pressure to chronic (8 mo) treatment with vitamins E and C (6), which suggests that oxidative stress plays a role in maintaining hypertension with aging in female SHR, although the present data do not indicate that ANG II is involved in mediating the oxidative stress in aging females. We found previously that the increase in blood pressure with aging in female SHR is associated with greater expression of intrarenal endothelin (ET) than in young females (23). In addition, a specific ET type A receptor antagonist decreased blood pressure in aging female SHR, but not to normotensive levels (23), similar to the effect of losartan in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Studies in intact animals have shown a modulatory effect of estrogen on ET-1 effects in the cardiovascular system. While neither male nor cycling female SHR rats show a role for ET-1 on hypertension, ET-1 protein levels are upregulated in postcycling SHR females with a consequent effect of ET-1 modulation on blood pressure (90,112). Similarly, in a rat model of DOCA-salt hypertension, ovariectomy worsened ET-1-mediated vasoconstriction, which could be reversed by supplementation with exogenous estrogen with or without progesterone (24).…”
Section: Sex Hormones and Endothelinmentioning
confidence: 99%
“…The oxidative stress markers are increased in women after menopause (37), and oxidative stress has caused the increase of blood pressure by decreasing the bioavailability of vasodilator (36). However, antioxidant therapy did not produce a reduction in blood pressure, in humans (38). The role of oxidative stress in hypertension in women after menopause has not been completely elucidated (35).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%